1997
DOI: 10.1093/jn/127.6.1084
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipids Modulate Bone Prostaglandin E2 Production, Insulin-Like Growth Factor-I Concentration and Formation Rate in Chicks ,

Abstract: This study examined the effects of dietary fat on the fatty acid composition of liver and bone, and on the concentration of insulin-like growth factor-I (IGF-I) in liver and bone, as well as the relationship of these factors to bone metabolism. Day-old male broiler chicks were given a semipurified diet containing one of four lipid sources: soybean oil (SBO), butter+corn oil (BC), margarine+corn oil (MAC), or menhaden oil+corn oil (MEC) at 70 g/kg of the diet. At 21 and 42 d of age, chicks fed MEC had the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 26 publications
5
103
0
5
Order By: Relevance
“…Several studies confirmed that dietary lipids could modulate the fatty acid profile in cartilage and bone tissues in growing chicks (Watkins et al, 1997). The mechanisms by which dietary fat influences the cartilage and bone metabolism and function are not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that dietary lipids could modulate the fatty acid profile in cartilage and bone tissues in growing chicks (Watkins et al, 1997). The mechanisms by which dietary fat influences the cartilage and bone metabolism and function are not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in young birds, several studies have shown that dietary n-3PUFA has a positive effect on the development, growth and modeling of long bones in growing chicks (Watkins et al, 1997) and growing Japanese quail (Liu et al, 2003), which have a direct and important role in facilitating the mineralization of bone tissues and strength of bone (Liu et al 2003). Also, it is well established that dietary lipids can modulate the fatty acid profile in cartilage and bone tissues (Watkins et al, 1997). By contrast, this study began dietary treatments at 56 weeks of age until hens were 68 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies have shown that a higher ratio of n-6 to n-3 fatty acids is associated with detrimental effects on bone health, and a lower ratio is associated with healthy bone properties (Watkins et al, 1997;Liu et al, 2003). Liu et al (2003) demonstrated that, in Japanese quail, long-term supplementation of n-3PUFA was beneficial to bone biomechanical properties that are involved in bone strength.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid methyl esters (FAME) were prepared from the tissue lipids using boron trifluoride (BF 3 ) in methanol (14%, w=w; Supelco Inc., Bellefonte, PA, USA) following the procedure of Watkins et al, (1997). For quantification of conjugated linoleic acid (CLA) isomers, lipids extracted from tissue samples were methylated (sodium methoxide) following the method of Li and Watkins (1998).…”
Section: Analysis Of Fatty Acidsmentioning
confidence: 99%